Study on the thermal stability of ordered mesoporous SiO2 film for thermal insulating film - Ha, Tae-Jung; Park, Hyung-Ho; Jang, Ho Won; Yoon, Seok-Jin; Shin, Sangwoo; Cho, Hyung Hee (ELSEVIER, 2012)
Ordered mesoporous SiO2 film has very low thermal conductivity compared to dense SiO2 film due to the presence of nanometer-sized pores. In order to apply this excellent material to thermal insulation fields, it is important to ensure the thermal stability of the pore structure at high temperature as well as thermal conductivity. In this study, ordered mesoporous SiO2 films were synthesized with various amounts of surfactant, and heat treatment at various temperatures was conducted with the synthesized films to confirm their thermal stabilities. Pore structure degradation of the mesoporous SiO2 film was observed with increasing temperature of the heat treatment as measured by grazing incidence small angle X-ray scattering. However, mesoporous SiO2 films with highly-ordered pore arrangements showed enhanced thermal stability and maintained their pore structures during additional heat treatment at higher temperatures. The mechanical properties and thermal conductivity of the ordered mesoporous SiO2 films with thermal stability at high temperature were analyzed. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: PORE-SIZE DISTRIBUTION; HYBRID THIN-FILMS; DIELECTRIC-CONSTANT; TIO2 FILMS; CONDUCTIVITY; CRYSTALLINE; MEMBRANE; DIOXIDE; DESIGN; OXIDE